Attitude of students towards the use of computer in education (2017)
The use of computer in education has increasingly become prominent in most part of the world. Therefore the study examined the attitude of students of St. Augustine College of Education, Akoka, Lagos. Simple random sampling technique was used to select 175 respondents. The instrument used for data gathering was a questionnaire with a reliability coefficient of 0.73. Descriptive statistics and T-test was used to analyze the data. The study revealed that students have positive attitude towards the use of computer. Also, the study revealed that there is no significant relationship between the male and female perception of students attitude to computer use in education. Therefore, the study recommends that computer studies should be inculcated and made compulsory at all levels of education. Government should make adequate provision of computers to the schools at all levels. The teachers should be advised to encourage the female students to improve on their attitudes toward the use of computer in education to be at par with their male counterparts. Students should be motivated to incorporate ICT into the source of learning tools as personal assessment of their computer competence improved. Lastly, the schools should give proper maintenance culture to the students to handle the computer properly.